The Effect of Mind Mapping on Student’s Paragraph Writing of Eight-Grade Students at Smpn 7 Tarakan - Tepi, Maria Lilista; Setyawan, Farid Helmi; Eppendi, Jhoni (Universitas Borneo Tarakan, 2024)
This study aimed to investigate the significance of effects of mind mapping on student’s writing abilities. This study employed a quasi-experimental design. The research sample consists of two classes selected through purposive sampling techniques. Data was collected using writing tests administered during pretest and posttest to measure students’ writing abilities. The results indicated that the mean difference in the control class is higher than that in the experimental class. This is because the use of mind mapping is most effective when used with actively participating students. In contrast, in this study, students in the experimental class were less active during the learning process. On the other hand, in the control class, students actively played online an online game called Roblox. The Roblox game helped students expand their English vocabulary, which potentially aided their writing. From this study, it can be concluded that mind mapping is still effective in helping students improve their writing skills, although it was not maximized in this context. The results would be more significant if the students were actively engaged in the learning process.